QCD analysis of near-to-planar 3-jet events - Banfi, A; Marchesini, G; Dokshitzer, Y; Zanderighi, G (2000)
Perturbative QCD analysis is presented of the cumulative out-of-plane momentum distribution in the near-to-planar e+e- annihilation events, Kout ≪ Q. In this kinematical region multiple gluon radiation effects become essential. They are resummed with the single-logarithmic accuracy, which programme includes the 2-loop treatment of the basic radiation and matching with the exact script O sign (Q52) result. Dedicated experimental analyses of 3-jet event characteristics are of special interest for the study of the non-perturbative confinement effects.